Survei Pelaksanaan Pembelajaran Pendidikan Jasmani Olahraga dan Kesehatan Pada Masa Pandemi Covid-19: Tinjauan Di Madrasah Ibtidaiyah (MI) - Seni Oktriani; Nur Mahfuzah Agustin; Anang Setiawan (Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Until now, no one has given a statement that the corona virus pandemic (Covid-19) is over. It even tends to show that the number of transmissions is still fluctuating. This can have an impact on the implementation of face-to-face learning in schools without exception in physical education learning at every level of education, including at the Madrasah Ibtidaiyahlevel. The purpose of this study was to determine the course of the learning process for physical education, sports and health at the Madrasah Ibtidaiyahlevel in Indramayu Regency during the Covid-19 pandemic. The research method used is a survey with an instrument in the form of a questionnaire in the form of a google form. A total of 374 respondents consisting of physical education teachers, students, and parents of students have given their responses. The results show that the learning process of sports and health physical education in Madrasah Ibtidaiyah, Indramayu Regency is carried out according to circumstances (online, offline, and combined).It was also revealed that some respondents have not mastered the use of gadgets so that difficulties arise in the learning process and collecting assignments. However, these obstacles can be overcome with assistance from schools, the role of physical education teachers, student adjustments in learning, parental support, and the use of media for learning so that learning continues well. The conclusion is that the implementation of physical education learning in Madrasah Ibtidaiyah, Indramayu Regency is dominantly carried out online with some difficulties and overcomes them through various roles involved so that learning continues to run smoothly.